Survival Benefit of Surgery after Chemoradiotherapy for Stage III (N0–2) Non–Small-Cell Lung Cancer Is Dependent on Pathologic Nodal Response. Issue 10 (October 2015) - Ziel, Ellis; Hermann, Gregory; Sen, Neilayan; Bonomi, Philip; Liptay, Michael J.; Fidler, Mary Jo; Batus, Marta; Warren, William H.; Chmielewski, Gary; Sher, David J.
<x xml:space="preserve">Abstract</x> Introduction: The benefit of surgery (trimodality therapy [TMT]) after chemoradiotherapy (CRT) for patients with stage III non–small-cell lung cancer (NSCLC) is controversial, but nodal pathologic complete response (N-PCR) is accepted as a strong predictor of overall survival (OS). We compared the outcomes of patients treated with TMT versus CRT, focusing on the importance of N-PCR. Methods: Patients with stage III NSCLC treated with CRT or TMT from December 2004 through December 2012 were included; patients with N3 disease were excluded. Pathologic nodal response dichotomized surgical patients into N-PCR versus residual nodal disease (RND) groups. Actuarial OS, progression-free survival (PFS), and distant metastasis-free survival (DMFS) were compared between patients treated with CRT and TMT and between CRT and N-PCR/RND. Results: The cohort was composed of 138 patients (52% CRT and 48% TMT). The median OS was significantly higher after TMT than after CRT (81 versus 31.8 mo, p = 0.0068). This benefit was restricted to N-PCR (n = 50, 83.2 versus 31.8 mo, p = 0.0004), as RND (n = 19) experienced poor OS (16.1 mo). On multivariable analyses, N-PCR had superior OS (hazard ratio [HR], 0.38; p = 0.0012), PFS (HR, 0.42; p = 0.0005), and DMFS (HR, 0.42; p = 0.0007) compared with CRT. Conversely, there were trends for worse OS and PFS for RND versus CRT, although only inferior DMFS was significant (HR, 1.83; p = 0.04). Conclusions: Surgical patients with complete nodal clearance experienced superior survival, but those with RND fared no better than CRT alone. Mediastinal response may play an important role in the decision to proceed with surgical resection after CRT for stage III NSCLC.